Habitat – structure and form, design experience in teaching interior design. - Malec-Zięba, Emilia (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2023)
This paper is an attempt to take a closer look on this issue in the context of design experiments carried out in the Interior Design Studio by second-year Interior Design students, Faculty of Architecture and Fine Arts, Andrzej Frycz Modrzewski Krakow University. The formula adopted in the studio is seeking the form, analysing, building structures, experiencing, discussing and making presentations. In designing we refer to numerous disciplines. The design process combines both visual arts, technical and sociological disciplines. The project is conducted with reference to the issues of building a structure of specific content, with distinctive signs of a residential space. The idea of a residential space is built based on material and emotional categories, an analysis of structures that serve equivalent functions, as well as inspirations drawn from culture and science. The presented designs show the multifaceted nature of interpreting and understanding of the residential space. Design education is an endless process that is constantly changing despite the adopted rules and methods, thus making it continuously relevant to exchange experiences and update knowledge on the subject.